Pengaruh penambahan jantung pisang kepok (Musa paradisiaca Linn) terhadap karakteristik organoleptik dan proksimat abon berbagai jenis ikan air tawar - Sastri, Sastri; Andriani, Andriani; Fitri, Yulia (Jurnal SAGO Gizi dan Kesehatan, 2026)
Background: Although freshwater fish are highly nutritious, fish products are processed using traditional and limited methods. Shredded fish (abon) is a diversified product with high economic value and a long shelf life, but it has low fiber content. Saba banana blossom is a local ingredient that is rich in nutrients and fiber and can increase the fiber content of shredded fish products.Objective: This study aimed to analyze and conduct organoleptic tests on the addition of 25% saba banana blossoms to various types of shredded fish samples.Methods: An experimental design was employed using a non-factorial completely randomized design with three treatments and three replicates. Organoleptic tests were conducted in August 2025 at the Organoleptic Laboratory with 30 panelists, whereas chemical tests were performed at the Food and Agricultural Product Analysis Laboratory. Data analysis was performed using analysis of variance, followed by Duncan’s multiple range test if significant differences were observed.Results: Organoleptic tests on shredded tilapia, catfish, and carp with 25% saba banana blossom showed no significant effects on color (mean score 3.62; p>0.05), taste (mean score 3.63; p>0.05), aroma (mean score 3.68; p>0.05), and texture (mean score 3.51; p>0.05). Proximate analysis indicated that the highest moisture, ash, fat, protein, carbohydrate, and fiber contents were 4.34 %, 6.31%, 25.08%, 50.99%, 22.69%, and 1.41%, respectivelyConclusion: The addition of 25% saba banana blossom did not significantly affect the color, taste, aroma, or texture of the shredded carp, tilapia, and catfish. The highest average proximate values were observed for shredded catfish. Future studies should use other fish species and involve expert panels and consumers for organoleptic testing to obtain more accurate results.